Portable chlorophyll meter in monitoring and management of nitrogen in common bean cultivars - Filla, Vinicius Augusto; Coelho, Anderson Prates; Tiraboschi Leal, Fábio; Trombeta Bettiol, João Víctor; Borges Lemos, Leandro (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
More sustainable practices involving biological nitrogen fixation (BNF) and the use of portable chlorophyll meter in fertilization management are promising to increase nitrogen (N) use efficiency in the common bean crop. This study aimed to monitor N managements using a portable chlorophyll meter and its effects on agronomic attributes of Carioca-type common bean cultivars with indeterminate and determinate growth habits (‘IPR Campos Gerais’ and ‘IAC Imperador’). The experiment was carried out in a randomized block design (RBD), in a 2 Ã— 9 factorial scheme, with four replicates. The first factor consisted of the cultivars and the second factor of the N management. The data were subjected to analysis of variance by F test and, when necessary, the means were grouped by the Scott-Knott test at 5% probability level. The use of portable chlorophyll meter is a viable alternative for N monitoring and management in common bean, allowing the reduction of top-dressing N application, regardless of the cultivar used. Highlights The use of portable chlorophyll meter is a viable alternative for nitrogen monitoring and management in common bean. Management with chlorophyll meter reduced the need for chemical fertilizer application, saving 105 kg ha-1 of urea. Further studies are needed to better understand this technology under conditions with different genotypes, soils and production systems.